2022
DOI: 10.3390/ijerph20010735
|View full text |Cite
|
Sign up to set email alerts
|

Green Innovation in Regional Logistics: Level Evaluation and Spatial Analysis

Abstract: Green innovation is imperative for the high-quality and sustainable development of the modern logistics industry. It is also key for achieving the goals of peak emissions and carbon neutrality. This study provides a way of thinking about the evaluation of the green innovation level of the logistics industry. The variance inflation factor-variance coefficient method was employed to construct an evaluation index system of the regional logistics green innovation level (RLGIL) from three dimensions. Empirical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…after KT. This suggested that precise evaluation of pre-KT glucose tolerance might be an important factor for predicting PTDM [ 9 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…after KT. This suggested that precise evaluation of pre-KT glucose tolerance might be an important factor for predicting PTDM [ 9 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed univariate or multivariate logistic regression analysis and built a calibration plot by using the R packages “rms”, “cor”, “Hmisc”, “boot”,. Variance inflation factors of each factor was checked for multicollinearity [ 9 ]. The Hosmer-Lemeshow goodness of fit (GOF) test was performed to evaluate the certainty of the prediction model.…”
Section: Methodsmentioning
confidence: 99%